Acute peritonitis in a canine associated with the ingestion of two magnets with stomach and colon perforation. A case report - Rojas-Sánchez, Ernesto (2018)
A canine, Australian cattle dog, male, six months old, was received at the Pathology Service of the School of Veterinary Medicine, Faculty of Health Science, National University, Heredia, because the owner suspect of an intoxication. The dog has an acute death with a lot of abdominal pain, vomit and salivation. In the anatomy-pathologic study, when the abdominal cavity was opened, it is noted an acute severe inflammatory process fibrin-purulent with presence of vegetable and food content in the peritoneum, which origins are two perforations of 1 cm of diameter, one in the stomach and the other in the colon, both caused by the attraction of two magnets that the dog ate. The pathologies caused by the magnet intake are not common in dogs. Deaths due to magnets intake have been reported in pediatrics, but there are no cases reported in veterinary medicine.